TRIB3 regulates Cx43 expression in human granulosa cells via the Wnt/β-catenin signaling pathway: an in vitro study - Zhoujun Zhu; Jiaoyun Dong; Wei Liu; Lan Xia; Zhihong Niu (Journal of Ovarian Research)
Abstract Background Increased expression of tribbles pseudokinase 3 (TRIB3), which is attributed to increased levels of free fatty acids in the follicular fluid of women with obesity, is correlated with reduced oocyte developmental competence. Connexin 43 (Cx43) is a crucial element of gap junctions in human ovarian granulosa cells (GCs) and facilitates oocyte development. This study aimed to investigate whether high TRIB3 expression and decreased oocyte development potential is regulated by aberrant Cx43 expression in human GCs under high fatty acid culture conditions. Methods GCs from women undergoing in vitro fertilization were grouped by body mass index (BMI). The human granulosa-like tumor cell line (KGN) was exposed to palmitic acid (PA), and its effect on cell apoptosis, viability and proliferation was assessed. The effects of TRIB3 overexpression and knockdown on KGN cells were analyzed. Gene and protein expression, along with the activity of the Wnt/β-catenin signaling pathway, were analyzed using quantitative reverse transcription-PCR, western blotting, immunofluorescence staining, and co-immunoprecipitation. Gap junction function was assessed using a scrape loading/dye transfer assay. Results Fertilization rates declined in women with overweight or obesity. In the GCs of these women, TRIB3 and Cx43 were upregulated. The protein expression of TRIB3 and Cx43 increased in KGN cells exposed to PA. TRIB3 overexpression led to increased Cx43 expression, whereas TRIB3 knockdown resulted in reduced Cx43 expression. Further mechanistic investigations revealed that TRIB3 upregulated Cx43 by reducing the degradation of β-catenin in the Wnt signaling pathway. Conclusions TRIB3 overexpression can enhance Cx43 expression in human GCs by inhibiting the Wnt/β-catenin pathway, thereby reducing oocyte maturation rate. These findings could be used to improve the quality of female oocytes and enhance infertility therapy in the clinic.